1984
DOI: 10.1176/ajp.141.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in the treatment of neuroleptic-induced akathisia

Abstract: Fourteen patients with neuroleptic-induced akathisia were treated with propranolol in an open trial. All patients demonstrated substantial improvement of their akathisia; nine of the 14 obtained complete remission. Response was quite rapid, occurring within 24 hours in most cases. Doses required for improvement were low (30-80 mg/day), and side effects were few. Lithium-induced tremor improved considerably, but symptoms of parkinsonism and tardive dyskinesia showed little change. Preliminary results with certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Also, there was no change in the significance observed when drinking history markers were included. Other studies that have studied the efficacy of Propranolol [27] and Lorazepam [28] for treatment of akathisia have also reported time-course dependent alleviation of akathisia symptoms. There is substantial evidence that 5-HT2A antagonists are successful in treating akathisia symptoms, exclusively neuroleptic-induced akathisia [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there was no change in the significance observed when drinking history markers were included. Other studies that have studied the efficacy of Propranolol [27] and Lorazepam [28] for treatment of akathisia have also reported time-course dependent alleviation of akathisia symptoms. There is substantial evidence that 5-HT2A antagonists are successful in treating akathisia symptoms, exclusively neuroleptic-induced akathisia [29].…”
Section: Resultsmentioning
confidence: 99%
“…Akathisia is generally associated with the sense of inner restlessness, mental uneasiness, unrest, or dysphonia, which can be intense [31]. The occurrence and reduction in akathisia have also been evaluated in several studies that have used atypical antipsychotics including Clozapine [22], Olanzapine [23], Quetiapine [2426], Ziprasidone [27], and others.…”
Section: Resultsmentioning
confidence: 99%
“…Doses of 60–120 mg/day have been demonstrated to be effective and well-tolerated for reducing DRBA-A symptoms. 94 – 97 The hypothetical mechanism of action, shared by the alpha-2 agonist clonidine, 98 is suppression of compensatory noradrenergic signaling that may trigger psychomotor activation associated with akathisia. D 2 stimulation in the locus ceruleus normally inhibits norepinephrine outflow, 99 so it follows that reduced dopamine signaling caused by DRBAs subsequently increases norepinephrine signaling in the midbrain as part of a feedback response.…”
Section: Discussionmentioning
confidence: 99%
“… 101 Comparative studies have shown cyproheptadine, zolmitriptan, and vitamin B6 produce similar levels of DRBA-A symptom reduction when compared with a range of doses (40–120 mg/day) of propranolol. 102 – 104 Serotonin 5-HT 2A receptor antagonists, such as mirtazapine, 105 110 trazodone, 111 fluvoxamine, 112 zolmitriptan, 103 mianserin, 113 and cyproheptadine, 102 represent another class of treatments for DRBA-A. 114 Blocking this receptor likely plays a role in reducing symptoms by increasing downstream dopamine signaling in areas of the brain affected by DRBAs.…”
Section: Discussionmentioning
confidence: 99%